The Apocryphon of Jannes and Jambres the magicians : P. Chester Beatty XVI (with new editions of Papyrus Vindobonensis Greek inv. 29456+29828 verso and British Library Cotton Tiberius B. v f. 87) - Pietersma, Albert. (Religions in the Graeco-Roman World, 1994)
The focus of this volume is the editio princeps of Papyrus Chester Beatty XVI: The Apocryphon of Jannes and Jambres, composed in Greek, perhaps as early as the first century C.E. A full commentary accompanies the edited text. An introductory section discusses the numerous references to the two magicians, who appear in Jewish, Christian and Pagan literatures as Moses' crafty opponents at the time of Israel's exodus from Egypt. Their exploits are recounted in over half a dozen languages, from the Syriac east to the Latin west and from Egypt's deserts to King Alfred's court. The Apocryphon is placed in its Graeco-Roman context, but is also discussed as a backdrop for the Faust saga of European literature. A basic book for anyone interested in biblical and related literatures.